Enriching triboelectric signal characteristic toward vibration waveform recognition by electron-beam irradiation - Hu Bian; Fanzheng Zeng; Haoran Yu; Xingyi Song; Jia Liu; Xingke Zhao; Zhenming Chen; Chengmei Gui; Junjun Huang (Chemical Engineering Journal, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Electric field-assisted simultaneous microextraction of ultrashort- to long-chain perfluorocarboxylic acids prior to HPLC-MS/MS quantification - Fenghong Wei; Pei Wang; Junjun Hu; Yanping Zheng; Xiaojia Huang (Journal of Hazardous Materials, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Autonomous inverse modeling of complex groundwater systems via a physics-integrated large language model multi-agent framework - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Yingtao Hu (Water Research, 2026)

Two-Dimensional Magnetotelluric Inversion Using Adaptive Mixed Lp Norm Regularization - Junjun Zhou; He Zhao; Zhidan Long; Ningbo Bai; Xiangyun Hu (Pure and Applied Geophysics, 2026)

Reassessing the efficacy and safety of trimethoprim-sulfamethoxazole for Pneumocystis jirovecii pneumonia: a retrospective study - Yangmin Hu; Wei Hu; Danyang Li; Fen Lan; Wei He; Meng Chen; Difei Yao; Junjun Xu; Yujin Lai; Haibin Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Fabrication of extracorporeal mechanical energy harvesting and implantable triboelectric nanogenerators for self-powered medical devices - Zhenni Liu; Hu Bian; Cong Lin; Quan Chen; Jia Liu; Zhenming Chen; Jun Chen; Dongdong Fang; Junjun Huang (Chemical Engineering Journal, 2026)

Boron-doped secondary shell coordination architectures in iron single-atom catalysts boosts peroxymonosulfate activation and high-valent iron-oxo species formation for superior aquatic micropollutant purification - Junli Zheng; Shanhong Lan; Junjie Hu; Junjun Ma; Yajie Wu; Ceng Zeng; Hao Luo; Jinquan Wan; Qintie Lin; Junlong Xie (Journal of Environmental Sciences, 2026)

Use of stable nitrogen isotopes in atmospheric aerosol research - Jingqi Bai; Libin Wu; Qingzi Zhao; Ke Xin; Wei Hu; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2026)

An effective 3D inversion algorithm of CSEM and its application in geothermal exploration - Ningbo Bai; Zhiqiang Chen; Bo Han; Junjun Zhou; Wenlong Zhou; Guoshu Huang; Xiangyun Hu (Physics of the Earth and Planetary Interiors, 2026)

Coupled tectonic-climatic-oceanographic dynamics drove the evolution of foraminiferal diversity in South China during the Middle to Late Mississippian - Chao Liu; Junjun Qi; Pedro Cózar; Ismael Coronado; Fei Li; Weiqing Liu; Meng Li; Ping Wang; Xin Li; Xia Hu; Song Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Coupled evaluation of the pros and cons of fluorochemical industry for sustainable development - Xinyue Shao; Pei Wang; Zhenjun Zhang; Junjun Hu; Yonglong Lu (Journal of Cleaner Production, 2026)

Effective gauss-newton inversion for 3D magnetotelluric data with arbitrarily anisotropic conductivities - Junjun Zhou; Bo Han; Andreas Junge; Xiangyun Hu; Tiaojie Xiao; Zhidan Long; Ningbo Bai (Physics of the Earth and Planetary Interiors, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Genetic mechanism of deep zeolite-rich reservoirs: a case study of the Lower Wuerhe Formation in Junggar Basin - Tianxin Hu; Yongqiang Qu; Jian Wang; Junjun Zhou; Wenfeng Ge; Chenyu Fu; Haiguang Wu (Frontiers of Earth Science, 2025)

The CD40/CD40L Pathway Regulates the Aggressiveness of Ovarian Cancer Cells via the Activation of Regulatory B Cells - Shanshan Ma; Pengfei Chen; Suyang Guo; Liangliang Wang; Jialin Hu; Junjun Shao (Biochemical Genetics, 2025)

Flexible and safe navigation of autonomous underwater vehicles with input-dynamics move blocking - Yujie Tang; Zilu Wang; Junjun Xie; Liang Hu (Ocean Engineering, 2025)

Light absorption and molecular composition of brown carbon in Nanjing, China: Large contribution of biomass burning and secondary formation - Junjun Deng; Xinfeng Wang; Jialei Zhu; Wei Hu; Libin Wu; Pingqing Fu (Journal of Environmental Management, 2025)

Fast three-dimensional inversion of magnetotelluric data based on L-BFGS optimization - Ningbo Bai; Jiancheng Zhou; Xiangyun Hu; Bo Han; Junjun Zhou; Jian Yang; He Zhao (Journal of Applied Geophysics, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Differentiated landscape pattern transformation strategies drive territorial space carbon neutrality: A path exploration based on mixed land use units - Houbao Fan; Xiaobin Jin; Junjun Zhu; Zhouyao Zhang; Chunguang Hu; Han Hu; Xiaoya Du; Yinkang Zhou (Sustainable Cities and Society, 2025)

Suppressing sediment nutrient release via electrokinetic drainage of porewater: apparent paradox and underlying mechanisms - Danyang Wang; Xianqiang Tang; Rui Li; Yanping Hu; Junjun Gu; Zhenhua Wang (Journal of Environmental Management, 2025)

Tenacissoside G reverses paclitaxel resistance by inhibiting Src/PTN/P-gp signaling axis activation in ovarian cancer cells - Jiudong Hu; Yujie Hu; Xiangqi Zhang; Jingxian Zhang; Yangyun Zhou; Xiaohe Wang; Wenhui Wu; Junjun Chen; Yonglong Han (Journal of Natural Medicines, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Self-Assembled Arachidonic Acid Nanomicelles for Radiation-Induced Ferroptosis to Enhance Tumor Radioimmunotherapy - Jiadong Wang; Yueyue Jing; Li Liu; Pengfei Xing; Zheng Deng; Yifan Zhang; Xirui Wu; Bin Hu; Cai Zhang; Xianglong Sun; Yuqian Liu; Jiawei Liu; et al. (Chemical Engineering Journal, 2025)

Hydration and solution properties of fluorescently labeled wheat arabinoxylans following enzymatic hydrolysis - Jieya Wang; Yan Liu; Qingbin Guo; Junjun Li; Liang Zou; Xinzhong Hu (Food Hydrocolloids, 2025)

Laser-induced ZnxMnOx-rGO-C@LIG materials doped with diesel distillate for Zn-ion hybrid supercapacitors - Yuxia Wang; Hu Zou; Zhong Qi; Siyu Yang; Wenlong Jiang; Rui Zhang; Zhengchun Yang; Junjun Shi; Jie He; Peng Pan; Huayi Li (Chemical Engineering Journal, 2025)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

The spatiotemporal heterogeneity of microbial community assembly during pit fermentation of soy sauce flavor baijiu - Liang Yang; Xiaodong Huang; Jiafeng Hu; Hong Deng; Junjun He; Chunlin Zhang (Food Bioscience, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Dynamic analysis and simulations of a deep-sea floating mining vehicle multi-body system under real-world operating conditions - Jialuan Xiao; Ping Cheng; Junjun Cao; Rui Lin; Mengzhi Luo; Caoyang Yu; Baoheng Yao; Yongli Hu (Ocean Engineering, 2024)

Molecular composition and sources of free amino acids in atmospheric aerosols from Mt. Tai and a nearby city - Qingzi Zhao; Libin Wu; Xiaoli Fu; Wei Hu; Yajie Wang; Yuantao Wang; Ke Xin; Jingjing Meng; Siyao Yue; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2024)

Preparation of edible antibacterial films based on corn starch /carbon nanodots for bioactive food packaging - Yuqing Wu; Junjun Zhang; Xuetao Hu; Xiaowei Huang; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2024)

Phosphate-solubilizing bacteria improve the antioxidant enzyme activity of Potamogeton crispus L. and enhance the remediation effect on Cd-contaminated sediment - Yuxin Cheng; Junjun Yuan; Gongting Wang; Zhenzhen Hu; Wenqing Luo; Xin Zhao; Yali Guo; Xiaonan Ji; Wei Hu; Min Li (Journal of Hazardous Materials, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Acidity-activated degradable Mn-engineered silicon nanohybrids coordinated with iprodione for high-efficiency management of Sclerotinia sclerotiorum and nutrient enhancement to crops - Fengrui Zhang; Min Fang; Peijie Hu; Xiang Yao; Chunlin Yang; Zaiyu Lu; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2024)

Effects of acetyl groups on the prebiotic properties of glucomannan extracted from Artemisia sphaerocephala Krasch seeds - Haocheng Li; Gongda Wang; Ximei Yan; Xinzhong Hu; Junjun Li (Carbohydrate Polymers, 2024)

Reassessing the greenhouse effect of biogenic carbon emissions in constructed wetlands - Liping Hu; Ziqian Li; Lingwei Kong; Jun Wei; Junjun Chang; Wenqing Shi (Journal of Environmental Management, 2024)

Spatiotemporal expansion and methane emissions of rice-crayfish farming systems in Jianghan Plain, China - Haodong Wei; Zhiwen Cai; Xinyu Zhang; Jingya Yang; Junjun Cao; Ke Meng; Liangzhi You; Hao Wu; Qiong Hu (Agricultural and Forest Meteorology, 2024)

Numerical investigation on NO formation of staged oxy-fuel combustion in a 35 MW large pilot boiler - Junjun Guo; Teng Guo; Tai Zhang; Fan Hu; Pengfei Li; Zhaohui Liu (Fuel, 2024)

Study of aromatic extraction from light cycle oil from the viewpoint of industrial applications - Junjun Shi; Xiaojia Wu; Guojia Yu; Lei Xi; Hu Zou; Wei Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2024)

Increasing amounts of midwestern Tibetan Plateau vortices and their response to soil moisture distribution coupled with different synoptic systems - Yuxin Kuang; Jie Zhang; Zishu Miao; Zhiheng Chen; Junjun Li; Miaomiao Niu; Shiying Wu; Rui Hu (International Journal of Climatology, 2023)
Tibetan Plateau Vortices (TPVs) are important synoptic systems that affect precipitation over the Tibetan Plateau (TP) and downstream weather. By using daily reanalysis data provided by ECMWF and the objective identification methods, the study identified the basic spatiotemporal changes of TPVs, clustered the TPVs by different dynamic circulation types and explored the dynamic circulation background of the classified TPVs in the midwestern TP and their relationship with thermal factors, such as sensible heat and soil moisture. The results show that TPVs in the midwestern TP exhibited an increasing trend from May to August, resulting from the coupling of dynamics with thermal forcing. The related synoptic circulations were divided into four types according to the dynamic circulations: the shortwave trough, the longwave trough, the shear line and the plateau anticyclone type. Among the TPVs, the percentage of TPVs in the shortwave and longwave trough type was relatively large, accounting for 48.7% and 31.5%, respectively, both of which were dominated by the coupling of increased sensible heat and decreased soil moisture. The shear line type was less affected by thermal factors, and mainly driven by dynamic factors, whereas the soil moisture gradient was responsible for the plateau anticyclone type. The simulation experiment also proved this conclusion.

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

The reduced Siberian spring snow cover modulation on southward northernmost margin of East Asia summer monsoon - Shiying Wu; Jie Zhang; Junjun Li; Zhiheng Chen; Yun Hang; Miaomiao Niu; Yuxin Kuang; Rui Hu (Climate Dynamics, 2023)

Quantitative assessment of the effects of zeolite alteration processes on deep clastic reservoirs – A case study of the Jiamuhe Formation in the Shawan Sag, Junggar Basin, China - Junjun Zhou; Haiguang Wu; Jian Wang; Guang Hu; Yunfeng Zhang; Jinlai Feng; Yilin Li (Marine and Petroleum Geology, 2023)

Positive and negative effects of marine transgression on the quality of lacustrine source rocks in the Upper Cretaceous Songliao Basin, China - Haiguang Wu; Chengcheng Feng; Xun Kang; Dawei Fu; Jinlai Feng; Yunfeng Zhang; Junjun Zhou; Tianxin Hu (Marine and Petroleum Geology, 2023)

Effects of personal carbon trading scheme on consumers' new energy vehicles replacement decision: An economic trade-off analysis - Jun Li; Lili Gao; Xianfeng Hu; Junjun Jia; Shanyong Wang (Environmental Impact Assessment Review, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

An efficient hybrid direct-iterative solver for three-dimensional higher-order edge-based finite element simulation for magnetotelluric data in anisotropic media - Junjun Zhou; Ningbo Bai; Xiangyun Hu; Tiaojie Xiao (Physics of the Earth and Planetary Interiors, 2023)

Mitochondria-associated endoplasmic reticulum membranes participate mitochondrial dysfunction and endoplasmic reticulum stress caused by copper in duck kidney - Junjun Peng; Xueyan Dai; Huiqin Fan; Chenghong Xing; Yu Zhuang; Xiaona Gao; Huabin Cao; Guoliang Hu; Fan Yang (Environmental Science and Pollution Research, 2023)

Comparison study of different forward modeling approaches by using the finite-element method for 3D magnetotelluric data in anisotropic media - Ningbo Bai; Bo Han; Xiangyun Hu; Junjun Zhou; Dan Zhu (Physics of the Earth and Planetary Interiors, 2023)

A visible colorimetric sensor array based on chemo-responsive dyes and chemometric algorithms for real-time potato quality monitoring systems - Yuqing Wu; Junjun Zhang; Xuetao Hu; Xiaowei Huang; Xinai Zhang; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2023)

Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes - Qiang Zhang; Wei Hu; Hong Ren; Jianbo Yang; Junjun Deng; Dawei Wang; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1 - Shuang Lin; Xueke Zhang; Ling Shen; Shuyuan Mo; Junjun Liu; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2022)

Differential Expression and Distinct Roles of Proteinase-Activated Receptor 2 in Microglia and Neurons in Neonatal Mouse Brain After Hypoxia-Ischemic Injury - Yicong Liu; Hui Li; Jiangqi Hu; Zhou Wu; Jie Meng; Yoshinori Hayashi; Hiroshi Nakanishi; Hong Qing; Junjun Ni (Molecular Neurobiology, 2022)

Three-Dimensional Finite-Element Analysis of Magnetotelluric Data Using Coulomb-Gauged Potentials in General Anisotropic Media - Junjun Zhou; Xiangyun Hu; Hongzhu Cai (Pure and Applied Geophysics, 2021)

Temporal variability of free-living microbial culturability and community composition after an Akashiwo sanguinea bloom in Shenzhen, China - Huirong Chen; Junjun JIang; Fajun Jiang; Shuangfei Li; Zhangli Hu (Ecotoxicology, 2021)

Reporter gene knock-in into Marc-145 cells using CRISPR/Cas9-mediated homologous recombination - Yanyan Chang; Junjun Shao; Yuan Gao; Wei Liu; Zhan Gao; Yonghao Hu; Huiyun Chang (Biotechnology Letters, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Performance of near real-time Global Satellite Mapping of Precipitation estimates during heavy precipitation events over northern China - Sheng Chen; Junjun Hu; Asi Zhang; Chao Min; Chaoying Huang; Zhenqing Liang (Theoretical and Applied Climatology, 2019)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Spatial relationship between climatic diversity and biodiversity conservation value - Junjun Wang; Ruidong Wu; Daming He; Feiling Yang; Peijun Hu; Shiwei Lin; Wei Wu; Yixin Diao; Yang Guo (Conservation Biology, 2018)
Capturing the full range of climatic diversity in a reserve network is expected to improve the resilience of biodiversity to climate change. Therefore, a study on systematic conservation planning for climatic diversity that explicitly or implicitly hypothesizes that regions with higher climatic diversity support greater biodiversity is needed. However, little is known about the extent and generality of this hypothesis. We used the case of Yunnan, southwest China, to quantitatively classify climatic units and modeled 4 climatic diversity indicators, including the variety (VCU), rarity (RCU), endemism (ECU) of climatic units, and a composite index of climatic diversity (CICD). We used 5 schemes that reliably identify priority conservation areas (PCAs) to identify areas with high biodiversity conservation value. We then investigated the spatial relationships between the 4 climatic diversity indicators and the results of the 5 PCA schemes and assessed the representation of climatic diversity within the existing nature reserves. The CICD was the best indicator of areas with high conservation value, followed by ECU and RCU. Contrary to conventional knowledge, VCU was not positively associated with biodiversity conservation value. The rarer or more endemic climatic units tended to have higher reserve coverage than the more common units. However, only 28 units, covering 10.5% of the land in Yunnan, had >17% of their areas protected. In addition to climatic factors, topography and human disturbances also significantly affected the relationship between climatic diversity and biodiversity conservation value. Our results suggest that climatic diversity can be an effective surrogate for establishing a more robust reserve network under climate change in Yunnan. Our study improves understanding of the relationship between climatic diversity and biodiversity and helps build an evidence‐based foundation for systematic conservation planning that targets climatic diversity in response to climate change.

Effects of endogenous salicylic acid synthesized through PAL and ICS pathway on baicalin and baicalein accumulation in Scutellaria baicalensis Georgi - Hu Su; Chao Yu; Junjun Shang; Xin Yan; Pengfei Liao; Youlin Zhu; Yanchun Gong; Bin Zeng (Acta Physiologiae Plantarum, 2016)

Application of land-use change model in guiding regional planning: A case study in Hun-Taizi River Watershed, Northeast China - Miao Liu; Yuanman Hu; Wei Zhang; Junjun Zhu; Hongwei Chen; Fengming Xi (Chinese Geographical Science, 2011)

SiRNA against Fabp5 induces 3T3-L1 cells apoptosis during adipocytic induction - Xi Ma; Xia Ren; Pengfei Han; Shengdi Hu; Junjun Wang; Jingdong Yin (Molecular Biology Reports, 2010)